Associational Structures and Beyond: Evolution and Contemporary Articulations of Bhumihar Caste Associations in Bihar, India. Issue 4 (7th December 2020) - Nandan, Aniket; Santhosh, R.
Abstract: This paper examines the historical development, growth, and contemporary articulations of the Bhumihar caste associations in Bihar by focusing on their relationship with land, political economy, and ideological orientations. As a landowning upper caste, the Bhumihars negotiated with a host of structural as well socio‐political transformations in the state primarily by constructing the self‐image of a warrior caste holding a Brahmin status. The paper in particular examines the impact of land reforms, violence unleashed by the Bhumihar caste militia during the agrarian unrest and the rise of Backward Caste mobilisation followed by the Hindutva mobilisation on the changing articulation of the Bhumihar caste associations. The paper also focuses on the emergence of the Bhumihar middle class and points out that through a visible process of culturalisation, the Bhumihars are able to maintain their exclusivity and purported superiority in the contemporary Bihar society even while upholding the mantle of Hindutva unity along with other lower castes.